Comparison of various methods of ischaemic cardioprotection on vitality of rat heart grafts - Hložková, Jana; Scheer, Peter; Váňová, Ivana; Suchý, Pavel; Parák, Tomáš; Hlinomaz, Ota (Acta veterinaria Brno, 2017)
The aim of the study was to compare 4 modes of ischaemic cardioprotection using continuous prograde autologous blood perfusion of the coronary artery in two hypothermic modes (group A, B) or conventional protection by cooled Hartmann solution (group C) or cooled saline (group D) without perfusion of the graft. Male Wistar rats (n = 24) were divided into four groups (A–D). In groups A (22–25 °C) and B (4–8 °C), blood perfusion rate was 10 ml/h and the graft was placed in a water bath. Groups C, D were initially rinsed with cold (4–8 °C) Hartmann solution (C) and cold saline solution (D), next the graft was placed in a water bath of cold (4–8 °C) Hartmann solution (C) or saline solution (D). The observed time was 30 min after the implemented perfusion (A, B) or initial rinsing (C, D). At 30 min, hearts of all the groups were perfused for 10 min with prograde-autologous arterialized blood at room temperature. At perfusion minute 10, blood was collected for biochemical analysis (sample 1). Sample 2 involved blood from a portable syringe infusion pumps (in parallel with sample 1). Pairwise test differences between samples 1 and 2 were significant in all the groups as regards creatine kinase and lactate dehydrogenase values, sampling 1 values being always higher, while cardiac troponin I concentrations were non-significant in the same comparison. The heart rate during the final perfusion was identical in all the groups. Our study has demonstrated that all observed cardioprotection modes are useful for experimental heart grafting.
Keywords: krysa rodu Rattus; obnova funkce; hypotermie; krystaloidní roztoky; Crystalloid Solutions; Recovery of Function; Hypothermia; studená ischemie; Cold Ischemia; přežívání štěpu; Rats; Graft Survival